Современные проблемы экологии Азово-Черноморского региона: Материалы III Международной конференции - Panov, B.N.; Southern Scientific Research Institute of Fisheries and Oceanography (YugNIRO) (Southern Scientific Research Institute of Marine Fisheries and Oceanography (YugNIRO), 2007)
Рассмотрены экологические аспекты состояния биоресурсов Черного и Азовского морей, актуальные проблемы природного заповедника Карадаг, состояние нерестовой популяции черноморской камбалы калкан, пиленгаса и внутривидовая неоднородность хамсы, зимующей у побережья Крыма. Описаны изменения качественного и количественного состава биоценозов Керченского пролива и Севастопольских бухт. Показано влияние антропогенного воздействия на экосистему Керченского предпроливья, рассмотрены экологические аспекты развития рекреационного хозяйства Керченского полуострова и вопросы сохранения природных экосистем Юго-Западного Крыма. Ecological aspects of the bioresources state of the Azov and Black Seas, current problems of the Nature Preserve Karadag, state of the Black Sea turbot and Pacific mullet spawning populations and intraspecific heterogeneity of anchovy wintering at the Crimea coast were considered. Changes of qualitative and quantitative composition of the Kerch Strait and the Sevastopol Bays biocenoses were described. Anthropogenic impact on the ecosystem of the area before the Kerch Strait was shown, ecological aspects of the recreation economy development of the Kerch Peninsula and issues of the South-Western Crimea natural ecosystems conservation were considered. Published